Home-grown school feeding in Latin America and the Caribbean: a review of 12 countries - Food Environment and Consumer Behavior Team; Alliance Bioversity International & CIAT (2022)
Despite a decade of implementation, HGSF models in LAC still face financial, institutional, and technological barriers, as well as sustainability challenges. Likewise, evidence on their impact is limited. Good practices, lessons learned, and valuable experiences from successes and failures have not been systematically and adequately assessed and analyzed, limiting their replication and expansion. This study, coordinated by the WFP Regional Bureau for Latin America and the Caribbean, in partnership with the Alliance of Bioversity International and CIAT, aimed at: 1) Undertaking a systematic assessment to consolidate and analyze the available evidence on the impacts of HGSF programs from 12 LAC countries that are part of WFP network 2) Identifying priority areas for future investment and intervention to fill existing knowledge gaps, with specific emphasis on those needed to inform decision-making by countries and implementation partners. The countries covered by this review include Bolivia, Brazil, Colombia, Cuba, Dominican Republic, Ecuador, El Salvador, Guatemala, Haiti, Honduras, Nicaragua, and Peru.